- #51

- 134

- 0

It can still be cleaned up some. Drop the zero and use the fact that -ln(b/a) = +ln(a/b).

Ok so I have now

R = L (ln(M/M-m)) = x

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter sg001
- Start date

- #51

- 134

- 0

It can still be cleaned up some. Drop the zero and use the fact that -ln(b/a) = +ln(a/b).

Ok so I have now

R = L (ln(M/M-m)) = x

- #52

gneill

Mentor

- 20,925

- 2,866

Ok so I have now

R = L (ln(M/M-m)) = x

That looks much neater.

- #53

- 134

- 0

That looks much neater.

Thanks again gneil!

- #54

- 134

- 0

sorry gneill!

Share:

- Replies
- 3

- Views
- 1K